Iris on the Move: Acquisition of Images for Iris Recognition in Less Constrained Environments - Matey, James R.; Naroditsky, Oleg; Hanna, Keith; Kolczynski, Ray; LoIacono, Dominick J.; Mangru, Shakuntala; Tinker, Michael; Zappia, Thomas M.; Zhao, Wenyi Y. (Proceedings of the IEEE, 2006)
Iris recognition is one of the most powerful techniques for biometric identification ever developed. Commercial systems based on the algorithms developed by John Daugman have been available since 1995 and have been used in a variety of practical applications. However, all currently available systems impose substantial constraints on subject position and motion during the recognition process. These constraints are largely driven by the image acquisition process, rather than the particular pattern-matching algorithm used for the recognition process. In this paper we present results of our efforts to substantially reduce constraints on position and motion by means of a new image acquisition system based on high-resolution cameras, video synchronized strobed illumination, and specularity based image segmentation. We discuss the design tradeoffs we made in developing the system and the performance we have been able to achieve when the image acquisition system is combined with a standard iris recognition algorithm. The Iris on the Move (IOM) system is the first system to enable capture of iris images of sufficient quality for iris recognition while the subject is moving at a normal walking pace through a minimally confining portal